Pengaruh Tingkat AI Augmented Decision Tools dan Kecepatan Respons Organisasi terhadap Tingkat Adaptabilitas Strategis Startup - Rusmini Icha Indryani; Lisna Nadila (Journal of Economics, Management, and Accounting, 2025)
This study aims to analyze the effect of AI Augmented Decision Tools and Organizational Response Speed on the Strategic Adaptability of Startups. A quantitative approach with a survey method was employed, involving 120 respondents consisting of CEOs, CTOs, and strategic managers from startups in Indonesia. The research instrument was a five-point Likert scale questionnaire, tested for validity and reliability, and met the classical assumption requirements. Data analysis was conducted using multiple linear regression. The results indicate that, partially, AI Augmented Decision Tools (Sig. = 0.000) and Organizational Response Speed (Sig. = 0.002) significantly affect the Strategic Adaptability of Startups. Simultaneously, both variables significantly influence adaptability (Sig. F = 0.000) with an Adjusted R² value of 0.412, indicating that 41.2% of the variation in strategic adaptability is explained by the research model. These findings support the Dynamic Capabilities and Organizational Agility theories, which place information technology and organizational agility as key factors in strategic adaptation. The study recommends integrating AI-based analytical systems with agile decision-making processes to enhance startups’ adaptability in facing market dynamics.